(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the issues of assessing the effectiveness of innovative activity in industrial enterprises, their theoretical and practical aspects. Innovative activity is interpreted as a key factor in the processes of increasing the competitiveness of the enterprise, increasing production efficiency, and introducing new technologies. When assessing innovative activity in the industrial sphere, economic, technological, social, and environmental factors are considered in close interrelation. The article highlights the system of main indicators used in determining the effectiveness of innovative activity, their methodological foundations and analytical approaches. At the same time, on the example of the experience of foreign countries, ways to improve the innovation management system at industrial enterprises are also indicated. When assessing the effectiveness of innovative activity, the possibilities of using integral indicators, the multi-criteria analysis method, and the investment return coefficient were analyzed.